COMPUTERIZED MEMBER SAVINGS FINANCIAL ADMINISTRATION COOPERATION - Rachmat Hidayat; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 1995)
In the recording system of money savings of members are still using manual systems cause less efficient time and labor. Routines that generate high enough, so part of daily treasurer has saturated, then the incoming data accuracy is reduced. Shape the new system was made with consideration of time efficiency and fast and accurate information. This new system is quite simple since the structure and operation can be easily understood and easy to follow procedure.